Análise de instanciações de gêneros de texto da família dos argumentos na abordagem sistêmico-funcional em livros didáticos de língua portuguesa para o ensino médio - Rossi, Angela Maria (2019)
This study aims to investigate texts that instantiate genres of the family of arguments and their purposes in high school Portuguese Language textbooks by focusing on Appraisal and Periodicity semantic-discursive systems. Therefore, the research is based on the theoretical-methodological perspective of Systemic Functional Linguistics (SFL), especially in studies on text genre analysis (MARTIN; ROSE, 2008, ROSE; MARTIN, 2012). We have adopted as a universe of analysis three high school Portuguese Language textbooks from the most distributed collection, from 2015-2017 (BRAZIL, 2015), offered by the Programa Nacional do Livro Didático (PNLD – Brazilian Textbook Program) to public elementary schools. We have selected the Português Linguagens, by Cereja and Magalhães (2013) as corpus, more specifically, the potential texts to instantiate the genres Exposition and Discussion used in chapters named Produção de textos. Analytical procedures followed the steps: a) analysis of the three constituent variables of the situation context that determine the register of the texts: field, tenor and mode (HALLIDAY, 1989; EGGINS; MARTIN, 1994; MARTIN; ROSE, 2007; MATTHIESSEN, 2015); b) analysis of the semantic-discursive Appraisal system (MARTIN, 1992, MARTIN; WHITE, 2005); c) analysis of the semanticdiscursive Periodicity system (MARTIN, 1992; MARTIN; ROSE, 2007); d) confirmation of the socio-communicative purpose of each text and the schematic structure of the genre (MARTIN; ROSE, 2008; CHRISTIE; DEREWIANKA, 2010; ROSE; MARTIN, 2012); finally, e) analysis and reflection of the results obtained in the previous procedures to verify how SFL genres perspectives can contribute to teach and learn reading and writing of argumentative genres – exposition and discussion – in the high school context (MARTIN; ROSE, 2008; CHRISTIE; DEREWIANKA, 2010; ROSE; MARTIN, 2012, EMILIA; CHRISTIE, 2013, HALLIDAY; MATTHIESSEN, 2014). This joint analysis showed that the corpus texts instantiate the exposition genre as dominant. Regarding the Appraisal semantic-discursive system, we have found a higher occurrence of the Attitude subsystem in the Arguments stage. These appraisal marks, both positive and negative, can be understood as enhancers of argumentative construction. In the Thesis stage, judgment and appreciation predominate. In regard to the Reiteration of the Thesis stage, appreciation and judgment are recurrent. Regarding the Periodicity semantic-discursive system, we observed that the texts follow a predictable rhythm, signaled by macroTheme, hyperTheme, as well as hyperNew and macroNew. These features, with more or less textual prominence, facilitate the development of the text, so that the reader can follow and understand it. The Thesis stage appears in hyperNew, the Arguments stage is in hyperThemes, and the Reiteration of the Thesis stage performs macroNew or hyperNew. Finally, we understand that few linguistic aspects are explored in relation to the characteristics of the exposition genre in high school Portuguese Language textbooks analyzed in this study.